The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1516-35982012000900019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and ruminal parameters of Holstein × Gir heifers fed sugarcane and increasing levels of crude protein

Abstract: -The objective of this study was to evaluate the effect of increasing levels of crude protein (CP) in the diet (13, 15, 19 and 22 g/100 g of dry matter, DM) on the metabolism and ruminal parameters of crossbred heifers fed forage sugarcane. Four crossbred Holstein × Gir heifers of average initial weight of 200 kg and average age of 14 months were used. The experimental design was in a 4 × 4 latin square. The intake values of DM, organic matter (OM), neutral detergent fiber (NDF) and non-fibrous carbohydrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
6
1
2
Order By: Relevance
“…These values are above the estimated for the feed formulation used, which estimated average intakes of diets at 2.36% body The results obtained in this study were higher than found by Queiroz et al (2012) that obtained means of 4.8 kg dry matter per day and 2.1% for BW for diet composed of 70% forage and 30% concentrate, on a dry matter basis, which contained 13 % crude protein, using sugar cane as forage for feeding dairy heifers, Holstein x Gir, with averaging 250 ± 50 kg of body weight and 19 months of age.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…These values are above the estimated for the feed formulation used, which estimated average intakes of diets at 2.36% body The results obtained in this study were higher than found by Queiroz et al (2012) that obtained means of 4.8 kg dry matter per day and 2.1% for BW for diet composed of 70% forage and 30% concentrate, on a dry matter basis, which contained 13 % crude protein, using sugar cane as forage for feeding dairy heifers, Holstein x Gir, with averaging 250 ± 50 kg of body weight and 19 months of age.…”
Section: Resultscontrasting
confidence: 80%
“…Soybean meal is the protein concentrate commonly used in dairy farming for being a feedstuff of proven high nutritional quality. Nevertheless, there is a growing interest from producers in information about alternative feeds, which can partially or totally replace the traditional ones, bringing reduction in the cost with feeding, as a consequence (QUEIROZ et al, 2012). Another important point to be checked during the growth of heifers is the body development.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of an efficient management of rearing females is the basis of any dairy production system, with significant participation in production costs (Queiroz, Berchielli, Signoretti, Ribeiro, & Morais, 2012). Tropical pastures are the main source of nutrients for this category of the animal due to the low cost and high convenience.…”
Section: Introductionmentioning
confidence: 99%
“…These diets subsequently affect ruminal biohydrogenation that could be an influence on fatty acid flow to the duodenum, and thus interfere with fatty acid muscle deposition (Scollan et al, 2014). Among the options for ruminant feed in Brazil, sugar cane and sugar cane bagasse have higher availability, and lower cost per unit of DM (Santos et al, 2011) compared with corn silage; however, they have nutritional limitations, such as a higher level of iNDF (Ezequiel et al, 2006;Queiroz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%